Acute Respiratory Distress Syndrome after Onyx Embolization of Arteriovenous Malformation - Isaac Tawil; Andrew P. Carlson; Christopher L. Taylor (Critical Care Research and Practice)
Purpose. We report a case of a 60-year-old male who underwent sequential Onyx embolizations of a cerebral arteriovenous malformation (AVM) which we implicate as the most likely etiology of subsequent acute respiratory distress syndrome (ARDS). Methods. Case report and literature review. Results. Shortly after the second Onyx embolization procedure, the patient declined from respiratory failure secondary to pulmonary edema. Clinical entities typically responsible for pulmonary edema including cardiac failure, renal failure, iatrogenic volume overload, negative-pressure pulmonary edema, and infectious etiologies were evaluated and excluded. The patient required mechanical ventilatory support for several days, delaying operative resection. The patient met clinical and radiographic criteria for ARDS. After excluding other etiologies of ARDS, we postulate that ARDS developed as a result of Onyx administration. The Onyx copolymer is dissolved in dimethyl sulfoxide (DMSO), a solvent excreted through the lungs and has been implicated in transient pulmonary side effects. Additionally, a direct toxic effect of the Onyx copolymer is postulated. Conclusion. Onyx embolization and DMSO toxicity are implicated as the etiology of ARDS given the lack of other inciting factors and the close temporal relationship. A strong physiologic rationale provides further support. Clinicians should consider this uncommon but important complication.